Large Epididymal Cyst: A Tale of Three Testes - Arora, Tanmay; Akami , Kewecho; Kapur , Neeti; Nain , Sameer (International Journal of Medicine, 2024)
Background: An epididymal cyst is a benign cystic structure that develops from the epididymis, typically due to a blockage in the epididymis, resulting in fluid accumulation. These cysts are generally harmless and noncancerous. Case Presentation: We examine the case of a 30-year-old male referred by the Psychiatry department for an assessment of the inguinal scrotal region, due to his belief that he had three testicles. Physical examination revealed an extratesticular, fluctuant, and cystic swelling easily palpable and distinct from the body of the left testis. Ultrasound findings showed a 2.3 x 1.7 cm fluid-filled lesion at the head of the epididymis. Intervention: Following a psychiatric evaluation, the patient underwent surgical excision of the cyst. Conclusion: The histopathological examination of the surgically removed cyst confirmed the diagnosis of an epididymal cyst, underscoring the importance of considering such benign conditions in differential diagnoses of scrotal abnormalities.